Electronic Trade: Advantages, Problems and «Sliding Effect» Arising under Transaction Costs Reduction - I. B. Nazarova; T. V. Dianova (Vestnik MGIMO-Universiteta)
The article entitled «Electronic trade: advantages, problems and «sliding effect» arising under transaction costs reduction» deals with the factors affecting the development of electronic trade and reveals the causes complicating its spread. Among the causes there are inability to have direct contact with purchased goods, infrastructure development problems, insufficient protection of in-formation, low trust to electronic transactions, legal regulation problems, low computer skills. The authors describe "sliding effect" which results in transaction costs reduction, leading to unreliability transforming the behavior of buyers based on researches to the behavior based on their stereotypes and brings buyers to loss of control under electronic transaction.